Application of The Situasional Leadership Style in PT. Bank Negara Indonesia (PERSERO) TBK, Mattoangin Branch Office Makassar - Andi Lisna B; Haedar Akib; Jamaluddin Jamaluddin; Andi Caesar To Taddampali; Nurfadillah Guntur (Pinisi Business Administration Review, 2021)
It is impossible to manage organizational members with different personalities, backgrounds, levels of willingness and abilities by using only a single leadership. Therefore, facing different situations or levels of employee maturity requires different leadership styles. This study aims to determine the Situational Leadership Style applied PT. Bank Negara Indonesia (Persero) Tbk, Mattoangin Branch Office Makassar, in terms of the dimensions of Telling Style, Selling Style, Participating Style and Delegating Style. The research method used is a descriptive research method with quantitative approaches. The data collection techniques used were questionnaires / questionnaire, structured interviews, direct observation and documents. The sampling technique used nonprobability sampling with saturated sampling (census) as many as 42 employees. Respondents' answers were analyzed using descriptive analysis through frequency distribution and percentage. The results of this study indicate that the application of a Situational Leadership Style which consists of four dimensions, namely the Telling Style is quite good and has a percentage of 77.30 %. Selling Style is good and has a percentage of 84.32%. Participating Style is very good and has a percentage of 85, 95%. Meanwhile, Delegating Style is good and has a percentage of 80.00%.